Direct short-term effects of EBP teaching: change in knowledge, not in attitude; a cross-cultural comparison among students from European and Asian medical schools - Widyahening, Indah S.; van der Heijden, Geert J.M.G.; Moy, Foong Ming; van der Graaf, Yolanda; Sastroasmoro, Sudigdo; Bulgiba, Awang (2012)
Introduction: We report about the direct short-term effects of a Clinical Epidemiology and Evidence-based Medicine (CE-EBM) module on the knowledge, attitude, and behavior of students in the University Medical Center Utrecht (UMCU), Universitas Indonesia (UI), and University of Malaya (UM). Methods: We used an adapted version of a 26-item validated questionnaire, including four subscales: knowledge, attitude, behavior, and future use of evidence-based practice (EBP). The four components were compared among the students in the three medical schools before the module using one-way ANOVA. At the end of the module, we measured only knowledge and attitudes. We computed Cronbach's α to assess the reliability of the responses in our population. To assess the change in knowledge and attitudes, we used the paired t-test in the comparison of scores before and after the module. Results: In total, 526 students (224 UI, 202 UM, and 100 UMCU) completed the questionnaires. In the three medical schools, Cronbach's α for the pre-module total score and the four subscale scores always exceeded 0.62. UMCU students achieved the highest pre-module scores in all subscales compared to UI and UM with the comparison of average (SD) score as the following: knowledge 5.04 (0.4) vs. 4.73 (0.69) and 4.24 (0.74), p<0.001; attitude 4.52 (0.64) vs. 3.85 (0.68) and 3.55 (0.63), p<0.001; behavior 2.62 (0.55) vs. 2.35 (0.71) and 2.39 (0.92), p=0.016; and future use of EBP 4.32 (0.59) vs. 4.08 (0.62) and 3.7 (0.71), p<0.01. The CE-EBM module increased the knowledge of the UMCU (from average 5.04±0.4 to 5.35±0.51; p<0.001) and UM students (from average 4.24±0.74 to 4.53±0.72; p<0.001) but not UI. The post-module scores for attitude did not change in the three medical schools. Conclusion: EBP teaching had direct short-term effects on knowledge, not on attitude. Differences in pre-module scores are most likely related to differences in the system and infrastructure of both medical schools and their curriculum.